Multicenter Experience with FRED Jr Flow Re-Direction Endoluminal Device for Intracranial Aneurysms in Small Arteries - (:unkn) unknown (AMER SOC NEURORADIOLOGY, 2017)
The authors assessed the clinical safety and efficacy of the Flow Re-Direction Endoluminal Device Jr (FRED Jr) dedicated to small-vessel diameters between 2.0 and 3.0 mm in 42 patients with 47 aneurysms. The primary efficacy end point of complete or near complete occlusion was reached at 1 month in 27/41 (66%), at 6 months in 21/27 (78%), and at 12 months in 11/11 (100%) aneurysms. BACKGROUND AND PURPOSE: Flow diverters are emerging as an endovascular treatment alternative for proximally located intracranial aneurysms. However, treatment of aneurysms at and beyond the circle of Willis is not well-established. We assessed the clinical safety and efficacy of the Flow Re-Direction Endoluminal Device Jr (FRED Jr) dedicated to small-vessel diameters between 2.0 and 3.0 mm. MATERIALS AND METHODS: This was a multicenter observational clinical study of 42 patients with 47 aneurysms treated by a flow-direction technique with the FRED Jr. The primary end point for clinical safety was the absence of death, major or minor stroke, and TIA. The primary end point for treatment efficacy was complete and near-complete occlusion according to the O'Kelly-Marotta grading scale at follow-up after 1, 6, and 12 months. RESULTS: The FRED Jr deployment was technically successful in all cases. In 39/42 (93%) patients, the primary safety end point was reached; in the 3 remaining patients, 1 disabling ischemic stroke, 1 minor stroke with complete recovery at discharge, and 1 TIA were observed. Two asymptomatic, completely reversible side-branch occlusions occurred. Angiographic (DSA or flat panel CT) and clinical follow-up were available after 1 month in 41/47 (87%), 6 months in 27/47 (57%), and 12 months in 11/47 (23%) aneurysms. The primary efficacy end point was reached at 1 month in 27/41 (66%), at 6 months in 21/27 (78%), and at 12 months in 11/11 (100%) aneurysms. CONCLUSIONS: Deployment of the FRED Jr is safe and effective in the treatment of intracranial aneurysms located in small vessels.
Keywords: PIPELINE EMBOLIZATION DEVICE; TERM FOLLOW-UP; ENDOVASCULAR TREATMENT; CEREBRAL ANEURYSMS; DIVERTING STENTS; EFFICACY; SAFETY; WILLIS; CIRCLE; LEVEL